2007
DOI: 10.1073/pnas.0609568104
|View full text |Cite
|
Sign up to set email alerts
|

Collapse of a fish population after exposure to a synthetic estrogen

Abstract: Municipal wastewaters are a complex mixture containing estrogens and estrogen mimics that are known to affect the reproductive health of wild fishes. Male fishes downstream of some wastewater outfalls produce vitellogenin (VTG) (a protein normally synthesized by females during oocyte maturation) and early-stage eggs in their testes, and this feminization has been attributed to the presence of estrogenic substances such as natural estrogens [estrone or 17␤-estradiol (E2)], the synthetic estrogen used in birth-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
1,097
5
20

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,754 publications
(1,161 citation statements)
references
References 30 publications
23
1,097
5
20
Order By: Relevance
“…NOECs range between 0.3 (or a calculated value of 0.16) and 1 ng/L, yet 100% feminization occurs at 3 ng/L and above. A SSD derived from the reproduction NOECs allows for a statistical derivation of the HC 5,50 and, therefore, a PNEC by considering all existing, relevant data for the 26 species that have been studied for reproductive effects. This approach further reduces the uncertainty associated with the fish data by considering data from other chordata demonstrating similar sensitivity to EE2 (e.g., frogs).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NOECs range between 0.3 (or a calculated value of 0.16) and 1 ng/L, yet 100% feminization occurs at 3 ng/L and above. A SSD derived from the reproduction NOECs allows for a statistical derivation of the HC 5,50 and, therefore, a PNEC by considering all existing, relevant data for the 26 species that have been studied for reproductive effects. This approach further reduces the uncertainty associated with the fish data by considering data from other chordata demonstrating similar sensitivity to EE2 (e.g., frogs).…”
Section: Resultsmentioning
confidence: 99%
“…The bootstrap simulation consisted of taking 2000 sets of n () 52) samples from the fitted distribution (with n ) 52 ) the number of data points used for the determination of the Best Fit distribution), and each time, the fifth percentile is calculated. The resulting distribution of HC5's is used to calculate the 50% confidence interval and the median value determined (HC 5,50).…”
Section: Nash Et Al 2005mentioning
confidence: 99%
See 1 more Smart Citation
“…EDCs consist of a wide range of natural and man-made chemicals, most of which are released to natural waters by anthropogenic activities and whose adverse effects on normal reproductive functions of aquatic species have widely been confirmed (Jobling et al, 1996;Routledge et al, 1998;Oehlmann, 2000;Irwin et al, 2001;Levy et al, 2004). For instance, widespread estrogenic chemical input has been regarded as an important factor related to the decline of fish abundance in freshwater systems (Jobling et al, 1998;Burkhardt-Holm et al, 2005;Kidd et al, 2007). Among this group of chemicals, steroid estrogens (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Despite small bioconcentration factors (BCFs 4-123), bioaccumulation of these seven target estrogenic chemicals could indeed occur in fish organisms (Chen et al 2014a, b;Lai et al 2002;Liu et al 2012;Huang et al 2015). Previous studies have reported adverse effects of estrogens, for example, feminization of fathead minnow in a lake by EE2 (Kidd et al 2007) and suppression of sexual behavior in male Japanese medaka by E2 (Oshima et al 2003). Xie et al (2010) observed fish feminization and altered development and reproduction in western mosquitofish (Gambusia affinis) from the Hanxi River (part of the Shima River) of the same region as the present study.…”
Section: Effect-directed Analysismentioning
confidence: 99%